A Life Histories Approach to Gold Prospecting and Frontier Farming in the Brazilian Amazon - Hoefle, Scott William (Journal for Geography, 2009)
In contrast to the usual faceless macro-economic and sociological treatment of development cycles in the Amazon, which at best offer generalities about ‘social actors’ labelled ‘peasants’, ‘ranchers’ and ‘trans-national corporations’, who represent the abstract categories of labour and globalised capital, a human face to frontier processes is offered here. The social and economic sustainability of the shifting back and forth from gold prospecting to family farming on the frontier is evaluated through the eyes of those who experienced it so producing an un-romanticised portrait of prospecting in western Pará during the gold rush of 1961-1990 as well as of frontier farming today. The economic origin and past quality of life of those who left local farms or came from the distant rural zones of impoverished Maranhão are compared and contrasted with that of their passage through the degrading living conditions of gold prospecting and finally with their current situation as struggling but independent frontier farmers in Itaituba and Santarém municipalities.